Low-temperature formation and stabilization of rare allotropes of cyclooctasulfur (β-S8 and γ-S8) in the presence of organic carbon at a sulfur-rich glacial site in the Canadian High Arctic. (1st March 2017) - Lau, Graham E.; Cosmidis, Julie; Grasby, Stephen E.; Trivedi, Christopher B.; Spear, John R.; Templeton, Alexis S.
Abstract: Large-scale deposits of elemental sulfur form annually on a glacier's surface at Borup Fiord Pass in the Canadian High Arctic. However, the mechanisms of mineralization and stabilization of elemental sulfur at this site are currently unknown. Here we show that X-ray diffraction (XRD) data for fresh sulfur precipitates collected from the surface of a melt pool over sulfide-rich ice reveal the presence of three sulfur allotropes, α-S8, β-S8, and γ-S8 (the three solid forms of cyclooctasulfur (S8 )). The detection of the β-S8 allotrope of elemental sulfur is notable, since β-S8 typically only forms in high temperature environments (>96 °C). The γ-S8 allotrope is also rare in natural settings and has previously been implicated as a signature of microbial sulfur cycling. Using combustion and infrared spectroscopy approaches, organic carbon is also detected within the sample bearing the three allotropes of elemental sulfur. Electron microscopy and scanning transmission X-ray microscopy (STXM) at the C K-edge show that the sulfur precipitates are intimately associated with the organic carbon at the submicron scale. The occurrence of β-S8 and γ-S8 in this low-temperature setting indicates that there are unknown pathways for the formation and stabilization of these rare allotropes of elemental sulfur. In particular, we infer that the occurrence of these allotropes is related to their association with organic carbon. The formation of carbon-associated sulfur globules may not be a direct by-product of microbial activity; however, a potential role of direct or indirect microbial mediation in the formation and stabilization of β-S8 and γ-S8 remains to be assessed.